Impact of treated domestic sewage water irrigation on crop nutrient, plant uptake and soil properties of cucumber cultivation - MHASKE, A.R.; MHASKE, T.A.; PANGUL, C.S. (Journal of Soil and Water Conservation, 2025)
The increasing global population has led to a surge in the demand for fresh water, as well as an increase in the amount of wastewater generated. To meet the growing need for water, domestic wastewater is being used for agriculture. In a recent study conducted during the years 2012-13 and 2013-14, cucumber (Cucumis sativus) crop was irrigated with both treated domestic sewage water (DTSW) and well water (WW). The results of the study demonstrated that the use of DTSW improved the physico-chemical properties of the soil, as well as the yield and nutrient status of the crops, when compared to the use of WW. After the harvest, the pH of the soil irrigated with DTSW was found to be within the range of 7.85, while that of WW was 7.93. The EC and OC were also higher in the soil irrigated with DTSW, with a mean of 0.43 dS m-1 and 5.44 g kg-1, respectively, compared to a range of 0.30 dS m-1 and 5.28 g kg-1, respectively in the soil irrigated with WW. The status of available N, P, and K were also found to be higher in the soil irrigated with DTSW, with a mean of 286.10 kg ha-1, 18.09 kg ha-1, and 443.30 kg ha-1, respectively, compared to a mean of 277.40 kg ha-1, 16.71 kg ha-1, and 435.20 kg ha-1, respectively in the soil irrigated with WW. The physical properties of the soil, such as BD and HC, were also examined. The results showed that the BD and HC of the soil irrigated with DTSW were 1.31 Mg m-3 and 1.48 cm hr-1, respectively, while that of the soil irrigated with WW were 1.41 Mg m-3 and 1.55 cm hr-1, respectively. The levels of micronutrients and heavy metals in both the soil and the crops were found to be below the phytotoxicity limits, indicating that the use of DTSW for irrigation did not pose a risk of toxicity to the plants or the soil. Overall, these findings provide valuable insights for commercial farmers and agricultural researchers regarding the appropriate management and use of DTSW for agricultural purposes.